itu Skema Pengamanan Data dengan Kombinasi Algoritma Advanced Encryption Standard (AES) dan Rivest Shamir Aldeman (RSA) - Sholihat Ruhaedi, Hedy; Rahmatulloh, Alam (Universitas Islam Balitar, 2024)
The rapid development of data drives the need for security in the data transmission process, with the aim of preventing access by unwanted parties to view the contents of the data sent. In order to achieve an optimal level of security, one of the strategies used is the application of cryptography. Cryptography using the Advanced Encryption Standard (AES) and Rivest Shamir Adleman (RSA) algorithms separately has often been used to protect the security of messages, whether in the form of text or digital images. This research will utilize a combination of the AES and RSA algorithms. This merger aims to ensure that the RSA algorithm can play a role in encrypting secret keys, while the AES algorithm is used to secure the original text (plaintext). The sender will receive the private key, encrypted secret key, and ciphertext. The recipient decrypts the secret key first using the RSA algorithm, and after obtaining the secret key, decrypts the ciphertext using the AES algorithm along with the previously decrypted secret key. It is hoped that this research will provide better security for sending information because the process of reading the contents of a secret message must go through both combination algorithms.